2017
DOI: 10.3390/f8010024
|View full text |Cite
|
Sign up to set email alerts
|

Spread of the Introduced Sitka Spruce (Picea sitchensis) in Coastal Norway

Abstract: Positive and negative effects on ecosystem services from plantation forestry in Europe have led to conflicts regarding non-native tree species. Sitka spruce (Picea sitchensis (Bong.) Carr.) is the most common plantation species in northwest Europe, covering 1.3 Mha. In costal Norway, Sitka spruce was intentionally introduced and is currently occupying about 50,000 ha. Sitka spruce was blacklisted in Norway in 2012, mainly based on the risk for invasive spreading, but little quantitative documentation exists on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…This conversion was not made in eastern Norway. Existing evidence suggests that past negative experiences with Sitka spruce that spread seeds beyond the plantation area may affect overall preferences for planted spruce (Nygård & Øyen, 2017;Saure et al, 2013).…”
Section: Survey Panel and Datamentioning
confidence: 99%
“…This conversion was not made in eastern Norway. Existing evidence suggests that past negative experiences with Sitka spruce that spread seeds beyond the plantation area may affect overall preferences for planted spruce (Nygård & Øyen, 2017;Saure et al, 2013).…”
Section: Survey Panel and Datamentioning
confidence: 99%
“…A possible motivation for such a study could be to obtain knowledge on the composition of a regenerating community at smaller spatial scales. In this case, information about the current stage of NNT establishment, dispersal distances, and site‐specific factors that influence NNT recruitment can be collected in plots or transects (Dyderski & Jagodziński, 2018 ; Nygaard & Øyen, 2017 ; Woziwoda et al, 2018 ). To assess local effects on biodiversity, additional ecological data such as cover and diversity of the herb layer may be collected as well (Woziwoda et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Forestation can also affect energy budgets of the surface and lower atmosphere via changes to biogenic aerosol regimes, which can affect atmospheric chemical and physical processes influencing both short-and long-wave radiation transfer (Spracklen, Bonn, & Carslaw, 2008;Unger, 2014 in Norway but has double the productivity (i.e., mean annual atmospheric CO 2 sequestration over the rotation period) to that of Norway spruce in the coastal regions of western Norway (Godal & Grønlund, 2014) where the largest total IFM + AFC candidate area potential is found. The reason behind the blacklisting of Sitka spruce is due to the potential threat on biodiversity outside plantations and further spreading, although some research has shown that such "invasion" threats can be greatly reduced if Sitka spruce plantations are given a 200 m buffer from protected areas (Nygaard & Øyen, 2017).…”
Section: Discussionmentioning
confidence: 99%